2019
DOI: 10.1111/adb.12793
|View full text |Cite
|
Sign up to set email alerts
|

Basolateral amygdala is required for reconsolidation updating of heroin‐associated memory after prolonged withdrawal

Abstract: Postretrieval extinction procedures are effective nonpharmacological interventions for disrupting drug‐associated memories. Nonetheless, the conditioned stimulus (CS) memory retrieval‐extinction procedure is ineffective in inhibiting drug craving and relapse after prolonged withdrawal, which significantly undermines its therapeutic potential. In the present study, we showed that, unlike the CS memory retrieval‐extinction procedure, noncontingent heroin injections (unconditioned stimulus [UCS]) 1 hour before th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Conversely, artificially activating glutamatergic BLA neurons during remote memory retrieval facilitates the destabilization of remote heroin memories, and restores the ability of weaker conditioned drug cues to initiate heroin memory reconsolidation. Collectively, these data suggest that remote memories for opioid reinforcement are at least in part stored in the BLA, and that modification of these opioid memories depends on synaptic neuroadaptations and neuronal activity in this structure (Yuan et al 2019). In addition to AMPAR, NMDARs are also required for the reconsolidation of morphine CPP memories (Zhai et al 2008).…”
Section: Reconsolidationmentioning
confidence: 94%
See 1 more Smart Citation
“…Conversely, artificially activating glutamatergic BLA neurons during remote memory retrieval facilitates the destabilization of remote heroin memories, and restores the ability of weaker conditioned drug cues to initiate heroin memory reconsolidation. Collectively, these data suggest that remote memories for opioid reinforcement are at least in part stored in the BLA, and that modification of these opioid memories depends on synaptic neuroadaptations and neuronal activity in this structure (Yuan et al 2019). In addition to AMPAR, NMDARs are also required for the reconsolidation of morphine CPP memories (Zhai et al 2008).…”
Section: Reconsolidationmentioning
confidence: 94%
“…Evidence suggests that after protracted withdrawal from heroin self-administration when memories are remote as opposed to recent, retrieval-extinction procedures are less effective. If instead of drug-conditioned cues, the unconditioned stimulus, heroin, is used to trigger memory retrieval, remote drug memories can again become labile and susceptible to interference by retrievalextinction procedures (Yuan et al 2019). This process may be mediated by the ability of drugs to temporarily reverse withdrawal-induced changes in glutamatergic synapses (Jedynak et al 2016;Spencer et al 2017;Madayag et al 2019).…”
Section: Reconsolidationmentioning
confidence: 99%
“…Inhibiting activity of GSK-3β in the BLA, but not the CeA, effectively disrupted reconsolidation of heroin cue memory and blocked subsequent drug-seeking behaviors. Many studies have demonstrated that BLA is involved in memory reconsolidation ( Wells et al, 2013 ; Yuan et al, 2020 ). However, the spcefic mechanism of GSK-3β in drug memory reconsolidation remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy may reflect distinct retrieval paradigms. Indeed, US retrieval has been shown to activate more memory traces and stronger protein alterations than CS retrieval (Liu et al, 2014;Xue et al, 2017;Yuan et al, 2019). Furthermore, we found that the pharmacological inhibition of Pi4KIIa in the BLA decreased GluA1 levels 1 h after US retrieval, and the genetic knockdown of Pi4KIIa impaired the enhancement of mEPSC frequency that was induced by US retrieval, suggesting a regulatory role for Pi4KIIa in GluA1 surface expression and synaptic efficacy in the rat BLA.…”
Section: Discussionmentioning
confidence: 65%